Meningkatkan Aktivitas dan Hasil Belajar Siswa dengan Model Pembelajaran Think Pair Share (TPS) Pada Materi Operasi Hitung Aljabar - Nur, Muhammad (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2021)
Learning is the main activity of the educational process. Researchers made observations in class VII A MTs. Darul Mukhlashin Tegalsiwalan and it was obtained 90% indicating that the student's score was ≤70. This research have a obtained to know about learning outcomes and also students activities with the learning model called TPS (Think Pair Share) on algebraic arithmetic operations material for class VII MTs. Darul Mukhlashin. This research was used type of CAR (Classroom Action Research). The procedure used is a cycle model. From the result of this research, learning activities in cycle I were on percentage of 60% and cycle II on 85%. And the result for learning outcomes of student in cycle I were obtained 60% dan 90% in the second cycle. This proves that the learning outcomes dan student activities can be increased by TPS model. For certain subjects, that model is used for avoiding feel boredom in learning activities.